Preparation method of yttrium ion doped sodium vanadium phosphate positive electrode material
The yttrium ion-doped vanadium phosphate composite material prepared by the hydrothermal assisted sol-gel method solves the problem of low working voltage of the positive electrode material of zinc ion and sodium ion battery, and achieves electrochemical performance with high specific capacity and long cycle stability.
Patent Information
- Application Number
- CN202510073832.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
AI Technical Summary
The positive electrode materials of existing zinc-ion batteries and sodium-ion batteries have low operating voltages, which leads to poor overall performance of these battery systems and makes it difficult to achieve high specific capacity and long cycle stability.
Through the hydrothermal-assisted sol-gel method, dodecyl trimethylammonium chloride is used as the morphological guiding agent and citric acid as the carbon source and chelating agent. Combined with heterogeneous element doping, carbon composite engineering and morphological engineering strategies, yttrium ion-doped vanadium phosphate composite material with a flower-like structure is prepared.
This method greatly improves the electronic conductivity of the material, forms a new conductive phase YPO4, changes the local charge distribution, forms an internal electric field, accelerates ion transport, suppresses structural strain, improves electrochemical performance, and achieves faster reaction kinetics and better cycling stability.
Smart Images

Figure CN119822351A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a yttrium ion-doped sodium vanadium phosphate positive electrode material, and belongs to the field of zinc ion batteries and sodium ion batteries. Background Art
[0002] With the development of economy and society and the improvement of human living standards, the global demand for energy has surged. At present, China's energy is widely dependent on non-renewable fossil fuels. The use and combustion of such resources will have a significant impact on the environment, including greenhouse gas emissions that cause climate change, which is inconsistent with the guiding principles of "carbon neutrality and carbon peak". Therefore, it is imperative to develop recyclable and renewable clean energy, and the development of large-scale energy storage systems is crucial to achieving green energy transformation and carbon neutrality goals. Among many energy storage systems, rechargeable batteries are regarded as one of the most promising energy storage systems due to their flexibility, environmental protection, ease of maintenance, high conversion efficiency and safety. In the emerging field of energy storage, LIBs are widely used in electric vehicles and portable electronic devices due to their high energy density and long life. However, due to the low abundance and uneven distribution of lithium resources in the earth's crust, their sustainable application faces challenges. In order to cope with the growing demand for energy storage technology from the rapid development of renewable energy, researchers have developed many other types of battery systems, such as ZIBs and SIBs. However, these two types of batteries have relatively lower operating voltages than LIBs. Therefore, in order to achieve satisfactory overall performance of these battery systems, researchers urgently need to design new high-voltage cathode materials with high specific capacity and long cycle stability.
[0003] Among many positive electrode materials, the polyanionic compound sodium vanadium phosphate (NVP) has the advantages of a higher voltage platform, good thermal stability and low voltage polarization, making it one of the ideal candidate materials for integrated high energy density energy storage batteries. In addition, NVP has a wide range of applications and can be used in a variety of battery systems such as zinc ion, sodium ion, organic and aqueous systems.
[0004] In the rational optimization of electrode structure, the heterogeneous element doping strategy can essentially rebuild the lattice structure and has been proven to be an effective method to improve electrochemical performance. The appropriate amount of doping of transition metal sites can improve the intrinsic conductivity while compensating for the capacity loss caused by structural collapse. Summary of the invention
[0005] The present invention provides a method for preparing a yttrium ion-doped sodium vanadium phosphate positive electrode material, comprising the following steps:
[0006] a) Dissolve the vanadium source, phosphate source, sodium source, morphology directing agent and heterogeneous element source in deionized water, mix well to obtain an orange solution, slowly add the carbon source powder, and then stir the solution at a stirring speed of 500 rpm for 3 hours to obtain a dark blue clear solution.
[0007] b) Place the obtained dark blue solution into a reactor and react under high pressure for 12 to 48 hours. After the reaction is completed, place the solution in a water bath at 85°C and stir until it becomes a gel.
[0008] c) The gel is placed in a vacuum oven for high-temperature drying, and after grinding, is placed in a porcelain boat and subjected to two-stage calcination annealing in a tubular furnace into which an inert gas is introduced. After grinding evenly, a flower-shaped sodium vanadium phosphate positive electrode material is obtained, which is applied to zinc ion batteries and sodium ion batteries.
[0009] Preferably, the temperature of the high-pressure reaction in the reactor is 180° C., and the reaction time is 12 h, 24 h, or 48 h.
[0010] Preferably, the selected inert gas is Ar or Ar / H2, the first stage calcination temperature is 350°C, the time is 4-6h, the second stage calcination temperature is 750°C, the time is 6-8h, and the heating rate is 5-8°C / min.
[0011] Preferably, the obtained flower-like sodium vanadium phosphate is a flower-like structure composed of nanosheets of 2 to 3 μm.
[0012] Preferably, the separator used in zinc ion batteries and sodium ion batteries is glass fiber.
[0013] In response to the demand for improvement of the existing sodium vanadium phosphate preparation technology, the present invention uses a hydrothermal-assisted sol-gel method, uses dodecyltrimethylammonium chloride as a morphology-directing agent, citric acid as a carbon source and chelating agent, and comprehensively uses heterogeneous element doping, carbon composite engineering and morphology engineering strategies to prepare a sodium vanadium phosphate composite material with a flower-like structure. The doping of the heterogeneous element Y greatly improves the electronic conductivity of the material, and forms a new conductive phase YPO4, changes the local charge distribution, forms an internal electric field, accelerates ion transmission, and plays the role of a structural strain inhibition phase, thereby improving the electrochemical performance. The flower-like structure composed of nanosheets increases the ion transmission channel and alleviates the volume change during the charge and discharge process, resulting in faster reaction kinetics and better cycle stability. Thanks to the above advantages, the prepared Y0.04-NVP material exhibits competitive electrochemical performance in both aqueous zinc ion batteries and organic sodium ion batteries. This work provides a new idea for obtaining high-rate and long-life aqueous and organic metal ion batteries. Compared with the prior art, the present invention has an advanced process flow, high product stability, and excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Of course, the drawings in the following description are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0015] Figure 1 The XRD diffraction patterns of the positive electrode materials in Examples 1, 2, 3 and Comparative Example 1 of the present invention are shown.
[0016] Figure 2 This is a SEM image of the positive electrode material in Example 1 of the present invention.
[0017] Figure 3 This is the Raman graph of the positive electrode material in Example 1 of the present invention.
[0018] Figure 4 This is a rate performance diagram of a zinc ion battery assembled with the positive electrode material in Example 1 of the present invention.
[0019] Figure 5 The zinc ion battery assembled with the positive electrode material in Example 1 of the present invention is 0.1 A g -1 The cycle performance diagram below.
[0020] Figure 6 This is a rate performance diagram of a sodium ion battery assembled with the positive electrode material in Example 1 of the present invention.
[0021] Figure 7 The sodium ion battery assembled with the positive electrode material in Example 1 of the present invention is 0.1 A g -1 Cycle performance diagram below DETAILED DESCRIPTION
[0022] The present invention provides a method for preparing a yttrium ion-doped sodium vanadium phosphate positive electrode material. The method comprises the following steps:
[0023] a) Dissolve the vanadium source, phosphate source, sodium source, morphology directing agent and transition metal element source in deionized water, mix well to obtain an orange solution, slowly add the carbon source powder, and then stir the solution at a stirring speed of 500 rpm for 3 hours to obtain a dark blue clear solution.
[0024] b) Place the obtained dark blue solution into a reactor and react under high pressure for 12 to 48 hours. After the reaction is completed, place the solution in a water bath at 85°C and stir until it becomes a gel.
[0025] c) drying the gel at high temperature in a vacuum oven, grinding it, placing it in a porcelain boat, and performing two-stage calcination annealing in a tubular furnace into which an inert gas is introduced, thereby obtaining a sodium vanadium phosphate composite material.
[0026] The temperature of the high-pressure reaction in the reactor of the present invention is 180°C, and the reaction time is 12h, 24h, or 48h. The inert gas selected during calcination is Ar or Ar / H2, the first stage calcination temperature is 350°C, the time is 4-6h, the second stage calcination temperature is 750°C, the time is 6-8h, and the heating rate is 5-8°C / min.
[0027] The separator of the present invention is a glass fiber separator (whatman); the zinc ion battery electrolyte is 3M Zn(OTf)2, and the sodium ion battery electrolyte is 1M NaClO4+EC / PC+5%FEC mixed solvent mixed solution. The materials are cut to a suitable size and directly used as electrodes to assemble R2032 button batteries.
[0028] In order to further illustrate the present invention, the preparation method of a yttrium ion-doped sodium vanadium phosphate positive electrode material provided by the present invention is described in detail below in combination with the examples, but it should not be understood as limiting the scope of protection of the present invention.
[0029] Example 1
[0030] Sodium vanadium phosphate cathode material was synthesized by hydrothermal-assisted sol-gel method. 4 mmol vanadium pentoxide, 12 mmol ammonium dihydrogen phosphate, 6 mmol anhydrous sodium carbonate, 0.16 mmol yttrium oxide and 0.2 g hexadecyltrimethylammonium bromide (CTAB) were added to 50 mL distilled water, stirred evenly, and then 12 mmol citric acid powder was slowly added and stirred at 80 °C for 3 h until the rich orange solution turned into a dark blue clear solution. Subsequently, the prepared dark blue solution was transferred to a polytetrafluoroethylene hydrothermal reactor and heated at 180 °C for 48 h. A brown suspension was obtained, which was stirred and evaporated at 85 °C in a water bath until a brown wet gel was obtained, and then the wet gel was placed in a vacuum dryer at 120 °C for 10 h. The dried dry gel was ground into a dark brown powder, placed in a tube furnace, and preheated at 350 °C in argon for 4 h at a heating rate of 5 °C / min. The solid powder after heat treatment was ground again and annealed at 750 °C for 6 h in Ar / H2 atmosphere to finally obtain Y0.04-NVP material.
[0031] The Y0.04-NVP powder obtained above was used as the active material, and the solvent NMP was added in a suitable proportion with the conductive carbon black and the binder PVDF. After stirring for 4-8 hours, the positive electrode slurry was obtained, and an automatic coating machine was used to coat it on the aluminum foil in a certain thickness. It was then vacuum dried in a vacuum oven at 80 °C for 10 hours, and the positive electrode sheet cut into a diameter of 12 mm was taken out. Zinc ion button batteries were assembled with the zinc sheet as the negative electrode; sodium ion button batteries were assembled in the glove box with the metal sodium sheet as the negative electrode, and the electrochemical performance was tested. The XRD diffraction pattern of the Y0.04-NVP material is shown in the figure. Figure 1 As shown in the figure, the XRD diffraction peak clearly points to the Na3V2(PO4)3 of NASICON structure, proving that the synthesized material has good crystallinity and high purity. In addition, the diffraction peak of YPO4 appears near 25.8°, proving that NVP / YPO4 heterogeneous structure is generated. The SEM image of Y0.04-NVP material is shown in the figure. Figure 2 As shown in Figure 1, the flower-like morphology is 2-3 μm in size. The material was tested by Raman, and the corresponding Raman spectrum is shown in Figure 1. Figure 3 As shown, the intensity ratio of D peak to G peak is 1.05. The rate performance and cycle performance of the material were tested. Figure 4 The rate performance diagram of zinc ion battery assembled with Y0.04-NVP sample at different current densities. Figure 5 The zinc-ion battery assembled for the Y0.04-NVP sample at 0.1 A g -1 The cycling performance diagram shows that after 100 cycles, its discharge specific capacity can still be maintained at 130.2 mAh g⁻¹, compared with its highest point of 131.3 mAh g⁻¹, the capacity retention rate is as high as 99%, and the coulombic efficiency is close to 99.9%. Figure 6 The rate performance diagram of the sodium ion battery assembled with the Y0.04-NVP sample at different current densities. Figure 7 Sodium-ion battery assembled for Y0.04-NVP sample at 0.1 Ag -1 Cyclic performance diagram of Y0.04-NVP. The initial discharge capacity of Y0.04-NVP is 134.7 mAh g -1 , it can maintain 130.0 mAh g even after 300 cycles -1 The high discharge specific capacity has a capacity retention rate of up to 97%.
[0032] Example 2
[0033] Sodium vanadium phosphate cathode material was synthesized by hydrothermal-assisted sol-gel method. 4 mmol vanadium pentoxide, 12 mmol ammonium dihydrogen phosphate, 6 mmol anhydrous sodium carbonate, 0.08 mmol yttrium oxide and 0.2 g hexadecyltrimethylammonium bromide (CTAB) were added to 50 mL distilled water, stirred evenly, and then 12 mmol citric acid powder was slowly added and stirred at 80 °C for 3 h until the rich orange solution turned into a dark blue clear solution. Subsequently, the prepared dark blue solution was transferred to a polytetrafluoroethylene hydrothermal reactor and heated at 180 °C for 48 h. A brown suspension was obtained, which was stirred and evaporated at 85 °C in a water bath until a brown wet gel was obtained, and then the wet gel was placed in a vacuum dryer at 120 °C for 10 h. The dried dry gel was ground into a dark brown powder, placed in a tube furnace, and preheated at 350 °C in argon for 4 h at a heating rate of 5 °C / min. The solid powder after heat treatment was ground again and annealed at 750 °C for 6 h in Ar / H2 atmosphere to finally obtain Y0.02-NVP material.
[0034] The Y0.02-NVP powder obtained above was used as the active material, and the solvent NMP was added in an appropriate proportion with the conductive carbon black and the binder PVDF. After stirring for 4-8 hours, the positive electrode slurry was obtained, and an automatic coating machine was used to coat the slurry on the aluminum foil at a certain thickness. Then, the slurry was dried in a vacuum oven at 80 °C for 10 hours, and the positive electrode sheet cut into a diameter of 12 mm was taken out. The zinc sheet was used as the negative electrode to assemble the zinc ion button battery; the sodium metal sheet was used as the negative electrode in the glove box to assemble the sodium ion button battery, and the electrochemical performance was tested.
[0035] Example 3
[0036] Sodium vanadium phosphate cathode material was synthesized by hydrothermal-assisted sol-gel method. 4 mmol vanadium pentoxide, 12 mmol ammonium dihydrogen phosphate, 6 mmol anhydrous sodium carbonate, 0.24 mmol yttrium oxide and 0.2 g hexadecyltrimethylammonium bromide (CTAB) were added to 50 mL distilled water, stirred evenly, and then 12 mmol citric acid powder was slowly added and stirred at 80 °C for 3 h until the rich orange solution turned into a dark blue clear solution. Subsequently, the prepared dark blue solution was transferred to a polytetrafluoroethylene hydrothermal reactor and heated at 180 °C for 48 h. A brown suspension was obtained, which was stirred and evaporated at 85 °C in a water bath until a brown wet gel was obtained, and then the wet gel was placed in a vacuum dryer at 120 °C for 10 h. The dried dry gel was ground into a dark brown powder, placed in a tubular furnace, and preheated at 350 °C in argon for 4 h at a heating rate of 5 °C / min. The solid powder after heat treatment was ground again and annealed at 750 °C for 6 h in Ar / H2 atmosphere to finally obtain Y0.06-NVP material.
[0037] The Y0.06-NVP powder obtained above was used as the active material, and the solvent NMP was added in an appropriate proportion with the conductive carbon black and the binder PVDF. After stirring for 4-8 hours, the positive electrode slurry was obtained, and an automatic coating machine was used to coat the slurry on the aluminum foil at a certain thickness. Then, the slurry was dried in a vacuum oven at 80 °C for 10 hours, and the positive electrode sheet cut into a diameter of 12 mm was taken out. The zinc sheet was used as the negative electrode to assemble the zinc ion button battery; the sodium metal sheet was used as the negative electrode in the glove box to assemble the sodium ion button battery, and the electrochemical performance was tested.
[0038] Comparative Example 1
[0039] Sodium vanadium phosphate cathode material was synthesized by hydrothermal-assisted sol-gel method. 4 mmol vanadium pentoxide, 12 mmol ammonium dihydrogen phosphate, 6 mmol anhydrous sodium carbonate and 0.2 g hexadecyltrimethylammonium bromide (CTAB) were added to 50 mL distilled water, stirred evenly, and then 12 mmol citric acid powder was slowly added and stirred at 80 °C for 3 h until the rich orange solution turned into a dark blue clear solution. Subsequently, the prepared dark blue solution was transferred to a polytetrafluoroethylene hydrothermal reactor and heated at 180 °C for 48 h. A brown suspension was obtained, which was stirred and evaporated at 85 °C in a water bath until a brown wet gel was obtained, and then the wet gel was placed in a vacuum dryer at 120 °C for 10 h. The dried dry gel was ground into a dark brown powder, placed in a tube furnace, and preheated at 350 °C in argon for 4 h at a heating rate of 5 °C / min. The solid powder after heat treatment was ground again and annealed at 750 °C for 6 h in Ar / H2 atmosphere to finally obtain NVP@NC material.
[0040] The NVP@NC powder obtained above was used as the active material, and the solvent NMP was added in an appropriate proportion with the conductive carbon black and the binder PVDF. After stirring for 4-8 hours, the positive electrode slurry was obtained, and an automatic coating machine was used to coat the slurry on the aluminum foil at a certain thickness. Then, the slurry was dried in a vacuum oven at 80 °C for 10 hours, and the positive electrode sheet cut into a diameter of 12 mm was taken out. The zinc sheet was used as the negative electrode to assemble the zinc ion button battery; the sodium metal sheet was used as the negative electrode in the glove box to assemble the sodium ion button battery, and the electrochemical performance was tested.
[0041] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a yttrium ion-doped sodium vanadium phosphate positive electrode material, characterized in that: Includes steps: (1) Dissolve the vanadium source, phosphate source, sodium source, morphology directing agent and heterogeneous element source in deionized water, mix well to obtain an orange solution, slowly add the carbon source powder, and then stir the solution at a stirring speed of 500 rpm for 3 hours to obtain a dark blue clear solution; (2) placing the obtained dark blue solution into a reactor and reacting under high pressure for 12-48 hours. After the reaction is completed, the solution is placed in a water bath at 85°C and stirred until it becomes a gel; (3) The gel is placed in a vacuum oven for high-temperature drying, and after grinding, is placed in a porcelain boat and subjected to two-stage calcination annealing in a tubular furnace into which an inert gas is introduced, and is taken out and ground to obtain a flower-like sodium vanadium phosphate composite material.
2. The method for preparing a yttrium ion-doped sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: In step (1), the vanadium source is vanadium pentoxide, the sodium source is anhydrous sodium carbonate, the phosphorus source is ammonium dihydrogen phosphate, the carbon source is citric acid, the morphology directing agent is dodecyltrimethylammonium chloride, and the transition metal source is yttrium nitrate.
3. The method for preparing a yttrium ion-doped sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: In step (2), the temperature of the high-pressure reaction in the reactor is 180°C, and the reaction time is 12 h, 24 h, and 48 h.
4. The method for preparing a yttrium ion-doped sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: In step (3), the selected inert gas is Ar or Ar / H2, the first stage calcination temperature is 350°C, the time is 4-6h, the second stage calcination temperature is 750°C, the time is 6-8h, and the heating rate is 5-8°C / min.
5. The method for preparing a yttrium ion-doped sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: The flower-like sodium vanadium phosphate obtained in step (3) is a flower-like structure composed of 2-3 μm nanosheets.
6. A sodium vanadium phosphate-based aqueous zinc ion battery and an organic sodium ion battery are prepared according to the preparation method according to any one of claims 1 to 5.